Evaluation of Factors Associated With Achievement of Biventricular Repair After Bilateral Pulmonary Artery Banding in Patients With Interrupted Aortic Arch. Issue 1 (January 2018) - Hirano, Yasuhiro; Inamura, Noboru; Kawazu, Yukiko; Aoki, Hisaaki; Kayatani, Futoshi; Iwai, Shigemitsu; Kawata, Hiroaki
Background: At our institution, we perform bilateral pulmonary artery banding (BPAB) as the first-stage palliation for interrupted aortic arch (IAA) with low birth weight or severe subaortic stenosis (SAS). The present study aimed to identify factors that may influence the decision regarding the type of second-stage operation, that is, univentricular palliation or biventricular repair, in these patients. Methods: Cardiac catheterization and angiographic data of nine patients with IAA who underwent initial BPAB and subsequent univentricular or biventricular repair were retrospectively analyzed. Results: Between 2004 and 2014, of nine patients with IAA who underwent initial BPAB, biventricular repair was subsequently performed in six patients (group B) and univentricular repair in three patients (group U). All patients survived. There was no significant intergroup difference in IAA classification, location of ventricular septal defect, presence of 22q11.2 deletion, presence of aberrant right subclavian artery, band diameter, or post-BPAB pulmonary artery pressure and index. Timing of BPAB and the body weight at the time of BPAB, however, differed significantly between the groups ( P = .02). Catheter data before BPAB were not significantly different between the groups, with the exception of the degree of subaortic stenosis (or hypoplasia of the left ventricular outflow tract) expressed as percentage of the normal end-systolic aortic valve annular diameter for patient body surface area. This metric (%SAS before BPAB) was significantly higher in group B (60%-68%) than in group U (47%-60%; P = .04). Among patients for whom baseline %SAS was < 60%, the %SAS did not increase after BPAB. Conclusion: The most important factor that allowed biventricular repair was not the pulmonary artery pressure or diameter but the degree of SAS. Patients who initially had more severe SAS ultimately underwent univentricular repair due to lack of substantial improvement in dimensions of the left ventricular outflow tract after BPAB.